Biochemical and Structural Insights on the Poplar Tau Glutathione Transferase GSTU19 and 20 Paralogs Binding Flavonoids - Sylvestre-Gonon, Elodie; Morette, Laura; Viloria, Morgane; Mathiot, Sandrine; Boutilliat, Alexis; Favier, Frédérique; Rouhier, Nicolas; Didierjean, Claude; Hecker, Arnaud (Frontiers in Molecular Biosciences, 2022)
Glutathione transferases (GST) constitute a widespread superfamily of enzymes notably involved in xenobiotic detoxification and/or in secondary metabolism. Populus trichocarpa genome (V4.1 assembly, Phytozome 13) consists of 74 genes coding for full-length GSTs and 9 likely pseudogenes. These GSTs are divided into 11 classes, in which the tau class (GSTU) is the most abundant with 54 isoforms. PtGSTU19 and 20, two paralogs sharing more than 91% sequence identity (95 % of sequence similarity), would have diverged in a common ancestor of Populus trichocarpa and Populus yatungensis species. These enzymes display the distinctive GSH-conjugation and peroxidase activities against model substrates. The resolution of the crystal structures of these proteins revealed significant structural differences despite their high sequence identity. PtGSTU20 has a well-defined deep pocket in the active site whereas the bottom of this pocket is disordered in PtGSTU19. In a screen of potential ligands, we were able to identify an interaction with flavonoids. Some of them, previously identified in poplar (chrysin, galangin, pinocembrin), inhibited GSH-conjugation activity of both enzymes with a more pronounced effect on PtGSTU20. The crystal structures of PtGSTU20 complexed with these molecules provide evidence for their potential involvement in flavonoid transport in P. trichocarpa.